A study on filterability of turbine base oil. (3rd July 2017) - Wu, Shixiong; Li, Shaoping
ABSTRACT: According to ISO 13357, the filterability of different turbine base oils is measured. It is found that the dry filterability of eight kinds of base oil is better than 100, but there are great differences in the wet filterability, which is significantly lower than respective dry filterability. The relationships between the difference of the filterability and the oil/water interfacial tension are investigated. The results show that the cause of the difference between dry and wet filterability is the hydrogen bonds and the oil/water interfacial tension for the same oil. As for the base oil with ISO viscosity grades (VG) 32, the wet filterability increases with the increase of the oil/water interface tension. On the other hand, the base oil with ISO VG 68, there is no significant correlation between oil/water interface tension and wet filterability.